(untitled) (Research, Society and Development, 2021)
With the increasing acceptance of the clinical use of bulk-fill resins, it is necessary to investigate the in vivo performance of these restorative materials. In this perspective, this systematic review to evaluate the clinical performance of Bulk-fill resins in restorations of vital, primary and permanent posterior teeth. PubMed, Cochrane, Scopus, LILACS, BBO and Capes publications search base were searched without restriction regarding the year of publication or language of the article. The inclusion criteria were clinical trials that evaluated the efficacy of resins composed of bulk-fill compared to the incremental technique. For the selection of articles and data extraction, two calibrated evaluators evaluated abstracts and complete articles. A total of 1443 abstracts were identified, of which 14 articles were included in the review. Of these, 01 was classified with a high level of evidence; 08 were moderate and 05 with a low level of evidence. The studies presented an average follow-up of the restorations of 35.1 months. A large part of the studies (75%) demonstrated that the occurrence of postoperative sensitivity. The high failure rate was more prevalent in class II restorations. The marginal adaptation/color change was material dependent and the occurrence of secondary caries in bulk-fill resin restorations was not significant concerning conventional resins in most studies. In the short term, the satisfactory clinical performance of bulk-fill resins used in primary and permanent restorations, with clinical outcomes and results equivalent to conventional composite resins were observed.